ANALISIS PENGGUNAAN MEDIA PEMBELAJARAN WORDWALL TERHADAP MINAT BELAJAR SISWA KELAS II B SDN 36 LUBUKLINGGAU - Aji Ramadhan; Fedilla Rossa Triyanti; Episiasi (EDUCATIONAL JOURNAL : General and Specific Research, 2025)
The purpose of this study was to analyze whether the use of wordwall learning media as interactive media has an impact on students' interest in learning at SDN 36 Lubuklinggau. This study uses a qualitative research type where data is collected using observation, interview, questionnaire, and documentation methods. The subjects of this study were all 15 students in class II B. The results of the observation revealed that the low interest in learning in class II B students was caused by students getting bored easily and being less active during learning so that students' understanding of the learning material given was less than optimal. However, by using this wordwall learning media, the results showed that class II B students became more active and enthusiastic in their learning process. This wordwall media can also increase students' interest in learning in class II B SDN 36 Lubuklinggau because wordwall media is an interactive media and can make the learning atmosphere fun because wordwall media combines sound and images so that students are interested and enthusiastic to participate in learning activities.